2008
DOI: 10.1016/j.clinbiochem.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Association of elevated plasma B-type natriuretic peptide levels with paroxysmal atrial fibrillation in patients with nonobstructive hypertrophic cardiomyopathy

Abstract: Conclusions:The present study indicated that plasma BNP level is clinically useful for identification of nonobstructive HCM patients who have a risk of PAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Although the increased levels of NT‐proBNP in patients with AF and HCM are well defined, the utility of this peptide has not been assessed to identify patients with HCM at risk for AF. Matsuura et al identified a plasma BNP cutoff level of 151.4 ng/L for distinguishing patients with HCM and PAF from those with NSR in among those with nonobstructive HCM without severe heart failure symptoms. In the current study, we evaluated NT‐proBNP rather than BNP, as NT‐proBNP circulates at a higher plasma concentration and also has a longer half‐life compared with that of BNP and seems to be a more accurate biomarker for detecting patients with LV diastolic dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Although the increased levels of NT‐proBNP in patients with AF and HCM are well defined, the utility of this peptide has not been assessed to identify patients with HCM at risk for AF. Matsuura et al identified a plasma BNP cutoff level of 151.4 ng/L for distinguishing patients with HCM and PAF from those with NSR in among those with nonobstructive HCM without severe heart failure symptoms. In the current study, we evaluated NT‐proBNP rather than BNP, as NT‐proBNP circulates at a higher plasma concentration and also has a longer half‐life compared with that of BNP and seems to be a more accurate biomarker for detecting patients with LV diastolic dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive examinations were performed, including M-mode, two-dimensional conventional Doppler, and color Doppler echocardiography 31) . Measurements were made according to the guidelines laid down by the American Society of Echocardiography 32) .…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%
“…127,131 Elevated NT-pro-BNP levels are associated with incipient LV remodelling and fibrosis assessed by cardiac magnetic resonance, could be used to diagnose insidious unfavourable LV remodelling and higher risk of sudden death in HCM. 67,123 A recent paper 132 proposes the clinical use of plasma BNP levels to identify non-obstructive HCM patients who are at risk of paroxysmal atrial fibrillation. As BNP is a marker of disease progression in non-obstructive HCM, serial assessment may provide non-invasive recognition of haemodynamic deterioration.…”
Section: Myonecrosis Markers: Troponinmentioning
confidence: 99%